PENGELOLAAN PROGRAM KEAKSARAAN FUNGSIONAL TINGKAT LANJUTAN DIKELURAHAN DADOK TUNGGUL HITAM KOTO TANGAH PADANG - Pelki Adi Putra (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2014)
This research was backgrounded by motivation height and believe in following Program benefit for students of functional literacy that leader by PKBM Pradana, in fact clearly in doing program, beginning from graduated functional literacy. The purposed of this research to know: a) to describe of planning program benefit for students of functional literacy, b) to describe of organization program benefit for students of functional literacy, c) to describe of method program benefit for students of functional literacy, d) to describe of leader program benefit for students of functional literacy, e) to describe of evaluation program benefit for students of functional literacy. The design of this research was descriptive quantitative, with subject of the research was the students in program benefit of functional literacy that leader by PKBM Pradana. The result of the research was the students of functional literacy with perception that the program of functional literacy doing was better.